Analysis of the harmonic excitation of scaffolding structures - Bęc, J.; Błazik-Borowa, E.; Szer, J. (Wydawnictwo Politechniki Łódzkiej, 2021)
Scaffoldings are lightweight temporary structures used mostly at construction sites. Due to their dynamic characteristics they are prone to dynamic excitation occurring at the structures or in the nearby at the construction site. A medium size scaffolding FEM model was subjected to harmonic excitation with frequencies ranging from 2 Hz to 12 Hz as a single harmonic force located in one of the selected nodal points. Full dynamic analysis of structure subjected to the load varying in time was provided by direct integration. Maximum displacement during forced vibrations and fading free vibrations after the source of excitation became inactive were watched in relation to the force parameters and its location. It has been observed that frequencies close to the first natural frequencies propagate to the entire structure, while higher frequencies cause discomfort for scaffolding users, but have a smaller range of action.
Keywords: scaffolding; harmonic excitation; dynamic analysis; direct integration; rusztowanie; wzbudzenie harmoniczne; analiza dynamiczna; integracja bezpośrednia